Neuronal and Glial Clocks Underlying Structural Remodeling of Pacemaker Neurons in Drosophila - Herrero, Anastasia; Duhart, José M.; Ceriani, Maria F. (Frontiers in Physiology, 2017)
A number of years ago we reported that ventral Lateral Neurons (LNvs), which are essential in the control of rest-activity cycles in Drosophila, undergo circadian remodeling of their axonal projections. This structural plasticity gives rise to changes in the degree of connectivity, which could provide a means of transmitting time of day information. Thus far, work from different laboratories has shown that circadian remodeling of adult projections relies on activity-dependent and -independent mechanisms. In terms of clock- dependent mechanisms, several neuronal types undergoing circadian remodeling hinted to a differential effect of clock genes; while per mutants exhibited poorly developed axonal terminals giving rise to low complexity arbors, tim mutants displayed a characteristic hyper branching phenotype, suggesting these genes could be playing additional roles to those ascribed to core clock function. To shed light onto this possibility we altered clock gene levels through RNAi- mediated downregulation and expression of a dominant negative form exclusively in the adult LNvs. These experiments confirmed that the LNv clock is necessary to drive the remodeling process. We next explored the contribution of glia to the structural plasticity of the small LNvs through acute disruption of their internal clock. Interestingly, impaired glial clocks also abolished circadian structural remodeling, without affecting other clock-controlled outputs. Taken together our data shows that both neuronal and glial clocks are recruited to define the architecture of the LNv projections along the day, thus enabling a precise reconfiguration of the circadian network.